Limitations of Embryo Selection Methods - Wong, Kai Mee; Repping, Sjoerd; Mastenbroek, Sebastiaan (Seminars in Reproductive Medicine, 2014)
In in vitro fertilization (IVF), the selection of embryos for transfer is generally based on the morphology of the available embryos. However, not all embryos with good morphology implant and on average only one in four treatments are successful. This has driven a quest for alternative selection methods. The best known alternative selection method is preimplantation genetic screening (PGS), which has been used for over a decade before it was shown to be inferior to morphological selection. Now, new forms of PGS (performing biopsy at another stage of development and new methods for analysis) are emerging, just like alternative noninvasive embryo selection methods. However, the concept that better selection will lead to improved IVF results is not so certain anymore. Evidence is accumulating that all available embryos in an IVF cycle can be cryopreserved and transferred in subsequent cycles without impairing pregnancy rates or maybe even with an improvement in pregnancy rates. Embryo selection will then no longer be able to improve the live birth rate in IVF; it could even lower the live birth rate. Embryo selection will only be able to improve the time to pregnancy, if embryos with the highest implantation potential are transferred first.
Keywords: assisted reproduction; embryo transfer; embryo selection; cryopreservation; IVF outcome